Accuracy of Multiple Pour Cast from Various Elastomer Impression Methods - Satheesh B. Haralur; Majed Saad Toman; Abdullah Ali Al-Shahrani; Abdullah Ali Al-Qarni (International Journal of Dentistry)
The accurate duplicate cast obtained from a single impression reduces the profession clinical time, patient inconvenience, and extra material cost. The stainless steel working cast model assembly consisting of two abutments and one pontic area was fabricated. Two sets of six each custom aluminum trays were fabricated, with five mm spacer and two mm spacer. The impression methods evaluated during the study were additional silicone putty reline (two steps), heavy-light body (one step), monophase (one step), and polyether (one step). Type IV gypsum casts were poured at the interval of one hour, 12 hours, 24 hours, and 48 hours. The resultant cast was measured with traveling microscope for the comparative dimensional accuracy. The data obtained were subjected to Analysis of Variance test at significance level <0.05. The die obtained from two-step putty reline impression techniques had the percentage of variation for the height −0.36 to −0.97%, while diameter was increased by 0.40–0.90%. The values for one-step heavy-light body impression dies, additional silicone monophase impressions, and polyether were −0.73 to −1.21%, −1.34%, and −1.46% for the height and 0.50–0.80%, 1.20%, and −1.30% for the width, respectively.